Late small bowel perforation from a migrated double plastic biliary stent: A case report and a review of literature of 85 cases from 2000 to 2022 - Ibraheem M. Alkhawaldeh (17430888) (2023)
Key Clinical Message This case highlights the importance of considering stent migration as a possible cause of intestinal perforation and the need for prompt surgical intervention. Endo-biliary stent displacement is rare but can cause intestinal perforation. An 85-year-old woman with a history of ERCPs and biliary stents experienced stomach pain and vomiting. She was diagnosed with small bowel perforation from migrated stents and underwent emergency laparotomy, bowel resection, and tension-free stapled anastomosis. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.7425